CULTURE BASED TOURISM STUDY IN NEW NORMAL ERA IN BADUNG DISTRICT - Belinda, Fera (UI Scholars Hub, 2020)
The tourism sector in Indonesia is rapidly declining due to the impact of the co-19 pandemic that occurred in various parts of the world, including in Indonesia. Entering a new era of normalcy, or a new normality of what is the condition of tourism in Indonesia, is it able to rise again and what is the strategy? Bali Province, can be said to be the epicenter of tourism in Indonesia. In this article discusses case studies in Badung Regency, related to culture-based tourism with qualitative research methods to analyze the data collected. The theory used is the theory of marketing communication, and also the theory of culture and local wisdom, for the results of the achievement are the level and interest of culture-based tourism in the new normal period, how health protocols are still applied to ensure the safety of visitors so they are not at risk of exposure to covid-19 but they can still communicate between one visitor with another visitor.